Selective Isolation and Molecular Characterization of Streptomyces sp from Dye Discharged Site and its Enzyme Screening in Prospective to Azo Dye Degradation - Rengaraj, Pavitra; Arunprasath, Raja; Pongiya, Uma Devi (Asian Journal of Biological and Life Sciences, 2026)
Background: Reactive azo dyes discharged from the textile industry have the great impact to the environment. The present study of using microorganism particularly Streptomyces sp from dye discharged site showed its effectiveness in the process of azo dye degradation. Materials and Methods: A laccase-producing Streptomyces sp. was isolated and initial Screening was performed followed by Morphological Characterization and Molecular Identification. Phylogenetic analysis and genetic analysis was also performed. Dye Decolorization Performance with respect to different carbon source was tested. Enzyme activity analysis includes reductase, manganese peroxidase and laccase was performed. Results: A reddish-brown colony on agar plates among the developed colonies (4 × 10⁴ CFU) showed that laccase was active. Morphological characterization showed that the colonies were white and powdery, with well-developed aerial and substrate mycelia and a spiral spore chain, which is typical of Streptomyces sp. Using 16S rRNA gene sequencing to identify the isolate at the molecular level confirmed that it was Streptomyces sp. Phylogenetic analysis showed that it was closely related to Streptomyces somaliensis, S. albu,S. sampsonii and S. hydrogenans. Genetic distance analysis revealed the greatest similarity with S. somaliensis (0.006974), succeeded by S. albus (0.00835), suggesting negligible evolutionary divergence. The distance matrix strongly supports the results of the phylogenetic tree, which show that isolate RP belongs to the genus Streptomyces and is most closely related to S. somaliensis. The isolate effectively decolorized Reactive Red dye, with carbon sources having a major impact. Dextrose (82.53±0.30%) caused the most decolorization, followed by starch (68.8±0.30%), lactose (45.46±0.2%), and sucrose (23.2±0.2%). Enzyme profiling showed that reductase had more activity (72.8±0.2 U) than manganese peroxidase (48.13±0.23 U) and laccase (23.87±0.30 U). Conclusion: These results show that several enzymes are involved in breaking down dyes, with reductase being the most important one. The study underscores the potential of laccase-positive Streptomyces sp. as an efficient biocatalyst for azo dye remediation.
Keywords: Amines; Azo reductase; Bioremediation; Laccase; Reactive red; Streptomyces sp